Cryopreserved human amniotic membrane for ocular surface reconstruction - Kruse, Friedrich E.; Joussen, Antonia J. M.; Rohrschneider, Klaus; You, Lingtao; Sinn, Brigitte; Baumann, Johanna; Völcker, Hans Eberhard (Graefe's archive for clinical and experimental ophthalmology, 2000)
Background: Amniotic membrane transplantation is used for the reconstruction of the ocular surface in the context of, for example, corneal ulcers or conjunctival scarring. The mechanisms by which preserved amniotic membrane grafts promote reepithelialization are unknown. As a first step the viability and proliferative capacity of amnion cells following cryopreservation of membranes in glycerol is investigated. · Methods: Fresh and cryopreserved (in 50% glycerol) amniotic membranes were investigated histologically and by vital stains. Following enzymatic digestion, amniotic cells were stained for viability and cultured in DMEM+10% FBS. In addition, explant cultures were established from fresh and cryopreserved membranes. · Results: Histologicacl examination showed no significant morphological alteration following cryopreservation. While fresh membranes contained predominantly vital cells, no such cells were detected following cryopreservation. Also, cells removed enzymatically from cryopreserved membranes were not viable and did not grow in culture. While both epithelial and fibroblastic cells grew from fresh membranes, no growth was seen from cryopreserved membranes. · Conclusion: The results suggest that the technique for preservation which is most widely used for ophthalmological amniotic membrane transplantation significantly impairs viability and proliferative capacity. This supports the clinical finding that neither immunological reactions nor signs of ingrowth of amniotic cells are observed in patients. Furthermore amniotic membrane grafts seem to function primarily as matrix and not by virtue of transplanted functional cells.